Strategi Implementasi Pendidikan Spiritual Quotient Dalam Meningkatkan Akhlak Mulia di MAN 2 Blitar - Arifin, M. Samsul; Jauhari, Moh. Irmawan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This research aims to analyze strategies for implementing spiritual intelligence in education as an effort to improve noble morals as well as being a role model for other educational institutions. This research was conducted at the Tunas Pratama Community Learning Activity Center, Blitar City with a descriptive qualitative method using a case study approach. Data was collected through in-depth interviews, participant observation and documentation. The research results show that the strategy for implementing spiritual quotient education at MAN 2 Blitar includes three stages, namely 1) strategic analysis using the environment and determining the formulation of mission, goals and policies; 2) implementation of spiritual education quotient with various programs managed by the religious team; 3) evaluation and control using direct and practical techniques.